Sex differences in the association of APOE ε4 genotype with longitudinal hippocampal atrophy in cognitively normal older people. (24th June 2019) - Shen, S.; Zhou, W.; Chen, X.; Zhang, J.
Abstract : Background and purpose: The aim of this study was to determine the effects of apolipoprotein E ε4 ( APOE ε4 ) genotype and sex together on longitudinal change in adjusted hippocampal volume [hippocampal volume:intracranial volume ratio (HpVR)] across the Alzheimer's disease (AD) continuum. Methods: At baseline, we included 372 individuals with normal cognition (NC), 738 individuals with mild cognitive impairment (MCI) and 271 patients with mild AD from the Alzheimer's Disease Neuroimaging Initiative database. We examined the effects of the APOE ε4 by sex interaction on longitudinal change in HpVR within the overall sample and within each diagnostic group. Results: Female gender was found to be associated with longitudinal reduction of HpVR in the NC and MCI groups, but not in the AD group. Similarly, APOE ε4 was associated with longitudinal reduction of HpVR in the NC and MCI groups, but not in the AD group. Further, female APOE ε4 carriers showed a greater longitudinal reduction of HpVR than their male counterparts in the NC group, but not in the MCI or AD group. However, due to the relatively short duration of follow‐up visits in patients with AD, further studies are needed to replicate these findings. Conclusion: Female APOE ε4 carriers show a greater longitudinal reduction of HpVR than their male counterparts in cognitively normal older adults.